2011
DOI: 10.1111/j.1746-1049.2011.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Market Development and the Rise and Fall of Backyard Hog Production in China

Abstract: With economic growth, the share of backyard hog production has declined in China over the past two decades. However, as backyard hog production fell in the rich, coastal regions, the backyard hog production from less wealthy, inland provinces has increased. In this paper, we illustrate the linkage between market development and patterns of household livestock production in rural China. The results indicate that rural labor and grain market developments have significant effects on household hog production. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…We expect that the same will be true for other organic waste, such as livestock waste and kitchen waste, though we do not provide more empirical evidence with respect to it, given data availability issues. For example, as the prevalence of backyard livestock raising in rural China is currently in decline (Qiao et al, 2011), how to properly use kitchen waste while conserving the environment will be a challenge in the future.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the same will be true for other organic waste, such as livestock waste and kitchen waste, though we do not provide more empirical evidence with respect to it, given data availability issues. For example, as the prevalence of backyard livestock raising in rural China is currently in decline (Qiao et al, 2011), how to properly use kitchen waste while conserving the environment will be a challenge in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Qiao et al. () found that the application of organic manure increased in poor areas due to more backyard livestock, and declined in rich areas. Poor areas are often located in mountainous regions with a higher degree of land fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of this inverted U-shaped relationship has been observed in many countries (Catelo, Narrod, & Tiongco, 2008;Adams & He, 1995;Rosenzweig & Wolpin, 1993;Devendra, 1993). The relationship has also been documented in China (Qiao, Chen, Carter, Huang, & Rozelle, 2011).…”
Section: Hog Production and Farmer Wealthmentioning
confidence: 90%
“…Hence, even though backyard producers would expand their herd sizes as their wealth increases from a low level, most of them would abandon hog production and move to other economic activities after their wealth level reaches a point. In other words, backyard hog production and wealth level have an inverted U-shaped relationship (Qiao et al, 2011). However, specialized medium and large-scale producers are more likely to focus solely on hog production, and their behavior can be explained by the profit-maximizing model, subject to credit constraints being eased if the business owner were to have more wealth (Varian, 1987).…”
Section: Econometric Modelmentioning
confidence: 99%